Catalytic substitution/cyclization sequences of O-substituted Isocyanates: synthesis of 1-alkoxybenzimidazolones and 1-alkoxy-3, 4-dihydroquinazolin-2(1H)-ones. Issue 97 (22nd November 2017) - Wang, Qiang; An, Jing; Alper, Howard; Xiao, Wen-Jing; Beauchemin, André M.
Abstract : O -Isocyanates are rare, but potentially useful intermediates: herein, their first metal-catalyzed cascade reaction yields complex heterocycles. Abstract : O -Substituted isocyanates ( O -isocyanates) have rarely been used in organic synthesis, given their tendency to undergo side reactions ( e.g., trimerization). Herein, we show that masked (blocked) O -isocyanate precursors allow one-pot or cascade reaction sequences featuring base-catalyzed substitution with 2-iodoanilines and 2-iodobenzylamines followed by copper-catalyzed cyclization, to form benzimidazolones and 3, 4-dihydroquinazolin-2(1 H )-ones. This work shows that O -isocyanates can serve as efficient building blocks for the synthesis of hydroxylamine-containing heterocycles.